PERILAKU KEUANGAN CASHLESS SOCIETY PADA MAHASISWA PENDIDIKAN EKONOMI FKIP UNTAN - Rahmah, Feny; Warneri, Warneri; Basri, Muhammad (Universitas Tanjungpura, 2024)
A cashless society is emerging as a result of technological advancements, posing problems like consumptive behavior and financial management issues. This study aims to examine how economic education students of FKIP UNTAN manage money in a cashless society. This study employs descriptive quantitative approach. The population is divided into three groups: groups 2020, 2021, and 2022 for the 2023